Analiza korelacji pomiędzy nasileniem cech osobowości a strategiami uczenia się leksyki na przykładzie polskich uczących się języka niemieckiego na trzecim etapie edukacyjnym - Jaroszewska, Anna; Milewski, Piotr; Posiadała, Katarzyna (Neofilolog, 2021)
<span class="NormalTextRun SCXW5502481 BCX0" data-ccp-parastyle="Normalny1" data-ccp-parastyle-defn=""ObjectId":"42446d94-3dd3-46ee-a4dd-dbf3ba4b23ce|170","ClassId":1073872969,"Properties":[134233614,"true",201340122,"2",201341983,"0",335559740,"276",469775450,"Normalny1",469778129,"Normalny1",469778325,"["heading 1","heading 2","heading 3","heading 4","heading 5","heading 6","Title","Subtitle"]"]">Developing learners' lexical subsystem is one of the most important tasks of foreign language didactics. The observable turn towards vocabulary (, Wortschatzwende’’) has contributed to an in-depth reflection on learners' lexical competence, including their strategic competence. The aim of this article is to present results of a correlational research concerning the influence of personality variables (understood according to the Five-Factor Model) on the range and frequency of strategies used by Polish high-school students to learn German vocabulary. The research project described in this article was conducted in April 2021. The polish adaptation of the NEO Five-Factor Inventory was applied to examine the learners’ personality traits. The Polish version of Schmitt's Vocabulary Learning Strategies Questionnaire (VLSQ) was used to investigate students’ preferred strategies for learning German vocabulary. Based on the conclusions from the research, an attempt was made to formulate practical guidelines for foreign language teachers concerning the possibilities of developing learners' lexical competence. The report is complemented by a list of open research questions and problems in this field.